Stock Returns under Interest Rate and Volatility Pressure with Green Innovation and Exchange Rate Roles: Return Saham di bawah Tekanan Suku Bunga dan Volatilitas dengan Inovasi Hijau dan Peran Nilai Tukar - Utami, Ni Ketut Widya; Atmadja, Anantawikrama Tungga; Musmini, Lucy Sri (Academia Open, 2025)
Background: The Indonesian capital market, particularly the property and real estate sector, is highly sensitive to macroeconomic fluctuations, especially during periods of global uncertainty such as 2020–2024. Specific Background: External factors like interest rates, inflation, and index volatility influence investor behavior and corporate performance, yet their interaction with sustainability dimensions remains underexplored. Knowledge Gap: Prior studies rarely assess the moderating role of green technology innovation and exchange rates in the macroeconomic–stock return relationship. Aims: This study investigates the impact of Bank Indonesia’s interest rate, index volatility, and inflation on stock returns, while testing the moderating effects of the Rupiah exchange rate and green technology innovation. Results: Interest rates and index volatility significantly reduce stock returns, while inflation is insignificant. The exchange rate shows no moderating effect. However, green technology innovation significantly moderates the relationship between interest rates and stock returns, indicating its buffering potential. Novelty: The inclusion of green innovation as a moderating variable presents a novel perspective in sustainable financial research within emerging markets. Implications: These findings suggest that adopting green innovations enhances corporate resilience to macroeconomic shocks and supports investor confidence, highlighting its strategic role in policy-making and ESG-oriented investment frameworks.Highlight : Interest rates and index volatility significantly reduce stock returns in the property sector. Green technology innovation moderates the impact of interest rates on stock returns. Exchange rate and inflation show no significant moderating effect on stock returns. Keywords : Stock Returns, Interest Rates, Index Volatility, Inflation, Green Technology Innovation, Exchange Rate